Rape as a weapon of war: advancing human rights for women at the U.S.-Mexico border - Falcón, Sylvanna M. (Social justice, 2001)
Part of a special issue on immigration and boundary policing in an era of globalization. The writer discusses rape as one of the consequences of militarization along the U.S.-Mexico border. Using data from nongovernmental organizations, government committees, and U.S. newspapers, she investigates specific cases of militarized border rape. She argues that national security rape, an instrument for bolstering a nervous state, and systematic mass rape, an instrument of open warfare, characterize the reality in the U.S.-Mexico border region. She comments on the factors associated with militarized rape and argues the need to promote human rights as a framework for assessing the circumstances in women's migration and the need to advance human rights in general for women in the border region.